Regulation of human subcutaneous adipose tissue blood flow. - Frayn, K; Karpe, F (2014)
Subcutaneous adipose tissue represents about 85% of all body fat. Its major metabolic role is the regulated storage and mobilization of lipid energy. It stores lipid in the form of triacylglycerol (TG), which is mobilized, as required for use by other tissues, in the form of non-esterified fatty acids (NEFA). Neither TG nor NEFA are soluble to any extent in water, and their transport to and out of the tissue requires specialized transport mechanisms and adequate blood flow. Subcutaneous adipose tissue blood flow (ATBF) is therefore tightly linked to the tissue's metabolic functioning. ATBF is relatively high (in the fasting state, similar to that of resting skeletal muscle, when expressed per 100 g tissue) and changes markedly in different physiological states. Those most studied are after ingestion of a meal, when there is normally a marked rise in ATBF, and exercise, when ATBF also increases. Pharmacological studies have helped to define the physiological regulation of ATBF. Adrenergic influences predominate in most situations, but nevertheless the regulation of ATBF is complex and depends on the interplay of many different systems. ATBF is downregulated in obesity (when expressed per 100 g tissue), and its responsiveness to meal intake is reduced. However, there is little evidence that this leads to adipose tissue hypoxia in human obesity, and we suggest that, like the downregulation of catecholamine-stimulated lipolysis seen in obesity, the reduction in ATBF represents an adaptation to the increased fat mass. Most information on ATBF has been obtained from studying the subcutaneous abdominal fat depot, but more limited information on lower-body fat depots suggests some similarities, but also some differences: in particular, marked alpha-adrenergic tone, which can reduce the femoral ATBF response to adrenergic stimuli.